Overcoming alcohol and other drug addiction as a process of social identity transition: the social identity model of recovery (SIMOR). (3rd March 2016) - Best, David; Beckwith, Melinda; Haslam, Catherine; Alexander Haslam, S.; Jetten, Jolanda; Mawson, Emily; Lubman, Dan I.
Abstract: In recent years, there has been an increasing focus on a recovery model within alcohol and drug policy and practice. This has occurred concurrently with the emergence of community- and strengths-based approaches in positive psychology, mental health recovery and desistance and rehabilitation from offending. Recovery is predicated on the idea of substance user empowerment and self-determination, using the metaphor of a "journey". Previous research describing recovery journeys has pointed to the importance of identity change processes, through which the internalised stigma and status of an "addict identity" is supplanted with a new identity. This theoretical paper argues that recovery is best understood as a personal journey of socially negotiated identity transition that occurs through changes in social networks and related meaningful activities. Alcoholics Anonymous (AA) is used as a case study to illustrate this process of social identity transition. In line with recent social identity theorising, it is proposed that (a) identity change in recovery is socially negotiated, (b) recovery emerges through socially mediated processes of social learning and social control and (c) recovery can be transmitted in social networks through a process of social influence.